Physics and radiobiology of nuclear medicine - Saha, Gopal B (Springer, 2001)
This second edition has been throughly updated and expanded, and prompted by the success of the first edition. Supplemented with tables and illustrations throughout the book, each chapter provides the reader with well-delineated descriptions of the different aspects of physics and radiation biology related to nuclear medicine. The last edition was successfull and highly acclaimed, as Dr. Saha made many complex concepts readily understandable for residents, students and practitioners in nuclear medicine. The book serves as an excellent text for nuclear medicine residents and technology students to prepare for their Board and Registry examinations. Special Features in the Second Edition include: Statistical tests: The Chi-Square test, the student t-test and linear regression; Internal dosimetry based on uptake variation; Digital computers: Data acquisition, filters, data processing; Coincidence detector gamma camera; Expanded chapter on radiation biology; Criteria for patient release and breast feeding; DOT regulations
Keywords: radiologie, nukleární medicína a zobrazovací metody; Nuclear Medicine; nukleární lékařství